Interactive QuickTime authoring wired media - Peterson, Matthew (San Francisco, Calif. : Morgan Kaufmann, 2004)
Interactivity is one of the most captivating topics for today's online community. It is a fast-growing field pushed by the rapid development and dispersion of Java, Shockwave, Flash, and QuickTime. While several good books are available about the interactive capabilities of Java, Shockwave, and Flash, until now there hasn't been a book about QuickTime interactivity. A logical follow-up to QuickTime for the Web, this eagerly awaited book by Matthew Peterson details the power of QuickTime's wired media technology and provides a resource for professionals developing and deploying interactive QuickTime content. This content can extend far beyond simple moviesit can act as application user interfaces, educational multimedia, scientific display panels, musical instruments, games and puzzles, etc., and can interact with you, your browser, a server, or with other movies. *Describes concepts and techniques of interactivity applicable to technologies beyond QuickTimeincluding Flash. *Features real-world, hands-on projects of progressive sophistication allowing developers to start with a project appropriate to their own level of QuickTime experience. *A companion CD-ROM contains the book's source code, tutorials, and demo software, including a demo version of Live Stage Pro (with a discount offer for the full version).
Foreword by Steven Gulie -- Preface -- What This Book Is and Is Not -- How to Read This Book -- Part I Background Information -- Chapter 1 What Is Interactive QuickTime? -- Chapter 2 How Do You Play an Interactive Movie? -- Chapter 3 The Stuff QuickTime Is Made Of -- Part II Wiring Existing Movies -- Chapter 4 Getting Familiar with the Tools -- Chapter 5 Customizing the Presentation of an Existing Movie -- Chapter 6 Digital Rights Management -- Chapter 7 Adding DVD Features -- Part III Sprite Worlds -- Chapter 8 A Simple World -- Chapter 9 Talking with Sprites -- Chapter 10 Collision Detection -- Chapter 11 Cel-Based Animation -- Chapter 12 User Interaction -- Chapter 13 Scripted Motion -- Chapter 14 Scripted Stretching -- Chapter 15 Cloning Sprites -- Chapter 16 Modeling Physics -- Part IV User Interfaces -- Chapter 17 Buttons -- Chapter 18 Sliders -- Chapter 19 Text Input -- Chapter 20 Menus -- Part V Multimedia -- Chapter 21 Audio and Video -- Chapter 22 Effects -- Chapter 23 Image Overrides -- Chapter 24 MIDI Instruments -- Chapter 25 Text Tracks -- Chapter 26 Flash Tracks -- Chapter 27 QTVR -- Chapter 28 MovieTracks -- Chapter 29 Third-Party Tracks -- Chapter 30 Other Tracks -- Part VI Communicating with the World -- Chapter 31 XML and QTLists -- Chapter 32 Loading Data -- Chapter 33 Setting Up a QTList Server -- Chapter 34 Sending Data to a Server -- Chapter 35 Exchanging QTLists -- Chapter 36 Communicating with the Browser -- Chapter 37 Dynamic Media -- Chapter 38 Intermovie Communication -- Chapter 39 Communicating with Applications -- Appendices -- Appendix A Useful Numbers -- Appendix B Math Functions -- Appendix C String Functions -- Appendix D QTList Functions -- Appendix E Programming Techniques -- Appendix F Sprite and Track Geometry -- Appendix G Graphics Modes -- Appendix H Codecs -- Appendix I General MIDI -- Appendix J Components -- Appendix K QTText Tags -- Appendix L HTML Embed Parameters -- Appendix M Wired Actions -- Appendix N Wired Constants -- Appendix O ASCII Table -- Appendix P Wired Sprites with Java -- Appendix Q Web Links -- Appendix R Contributing Developers -- Appendix S CD Contents.
Includes index.
Keywords: QuickTime; Interactive multimedia; Electronic books